The political and social economy of commodity control - Brown, Christopher P. (London : Macmillan, 1980)
This text broadens the theoretical consideration of control presented in the author's Primary Commodity Control (1975)
Includes index.
Includes bibliographical references: p. 338-365.
ijb, 17/01/2019
Loans
Keywords: Commodity control